B lineage acute lymphoblastic leukemia transformation in a child with juvenile myelomonocytic leukemia, type 1 neurofibromatosis and monosomy of chromosome 7 - Possible implications in the leukemogenesis - Scrideli, C. A.; Baruffi, M. R.; Rogatto, Silvia Regina [UNESP]; Valera, E. T.; Defavery, R.; Tone, L. G. (Elsevier B.V., 2003)
This report describes the case of an 8-month-old infant with a diagnosis of juvenile myelomonocytic leukemia (JMML) and type I neurofibromatosis that presented progression to B lineage acute lymphoid leukemia (ALL). The same rearrangement of gene T-cell receptor gamma (TCRgamma) was detected upon diagnosis of JMML and ALL, suggesting that both neoplasias may have evolved from the same clone. Our results support the theory that JMML may derive from pluripotential cells and that the occurrence of monosomy of chromosome 7 within a clone of cells having an aberrant neurofibromatosis type 1 (NFI) gene may be the cause of JMML and acute leukemia. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: myelodysplasic syndrome; JMML; neurofibromatosis type 1; monosomy 7; acute lymphoblastic leukemia; TCR gamma